Phytolith analysis of Cyperaceae from the Pampean region, Argentina - Fernández Honaine, Mariana (2009)
Cyperaceae, along with Poaceae, is the main silica accumulator. Although the anatomical-taxonomic and palaeobotanical relevance of phytoliths has been well established, there are no studies that deal with the qualitative and quantitative aspects of the phytolith production or differentiate phytoliths from the different organs in Cyperaceae. Toward the construction of a detailed database of phytolith production, we describe in the present paper the phytoliths of leaves, culms and fruits of Cyperaceae from Pampean region (Argentina). Phytoliths were extracted by a calcination technique. Qualitative and quantitative characters and percentages of phytolith morphotypes were subject to principal component analysis to analyse their taxonomic relevance. For some sedges, values of phytolith content and a comparative analysis of leaves, culms and fruit phytoliths are presented here for the first time. Diverse tissues such as epidermis, xylem, parenchyma and sclerenchyma produced phytoliths. The most abundant morphotypes were conical phytoliths, which showed differences in the base shape and in their size between organs. Leaf/culm cones have a rounded, rectangular or square base; typical fruit cones have a polygonal base and they are bigger and more robust. PCA showed that quantitative and qualitative characters of cones, along with the percentages of morphotypes, allowed group distinction.